5x + 6y = 7 SUBSTITUTION METHOD
2x + 2y = 4
5x + 6y = 7 Solve for either x or y in 1 of the 2 equations.
- 6y - 6y
-----------------------
5x = -6y + 7
----- ------ ----
5 5 5
x = -6/5y + 7/5
2(-6/5y + 7/5) + 2y = 4 Substitute the expression you got for x or y into
-12/5y + 14/5 + 2y = 4 the other equation.
-2/5y + 14/5 = 4
- 14/5 - 14/5
------------------------------
-2/5y = 6/5
-------- --------
- 2/5y - 2/5y
y = -3
5x + 6(-3) = 7 Plug in the value you got for y in step 2 into the
5x - 18 = 7 equation that you didn't use.
+ 18 + 18
------------------
5x = 25
--- -----
5 5
x = 5
(x,y) ⇒ coordinate
(5,-3) ⇒ final answer